Overcoming Silicon Limitations in Nanophotonic Devices by Geometrical Innovation: Review - Avi Karsenty (IEEE Photonics Journal)
In order to continue to fulfill the ever-increasing demands on ultra-fast microprocessors, a revolution in silicon photonics communication is necessary. Traditional CMOS, FinFET, and GAAFET downsizing techniques have started to near the physical limits of available materials. Although on-chip optical communication presents a promising direction for circumventing the scaling bottleneck, silicon-based solutions are constrained by several factors, such as the element's indirect energy band gap, limited absorption spectrum, native oxide, and more. However, the employment of recent innovative design geometries has enabled the development of a series of silicon nanophotonics and nanoelectronics devices that both overcome these limitations as well as improve on existing physical phenomena. Presented in this comprehensive review is a new, methodical approach showcasing examples of these Si nano-devices, which are part of a larger family of components being developed for optical communication and advanced sensing applications. After presenting stand-alone devices, we discuss concerns, considerations, trends and forecasts regarding their possible integration into nanophotonics modules and platforms.